The Use of Gadgets As E-Learning Basis during The COVID-19 Pandemic - Winning Amintas Kartika Waruwu Sari; Siti Mayang Sari; Jalaluddin Jalaluddin; Farida Win Sari Manurung; Sukarman Purba; Lambok Pamancar Saragi (International Conference on Multidisciplinary Research, 2022)
Since the pandemic started, online learning has been applied to replace the conventional one. Gadgets then become essential tools and the main information source for learning during this time.This study aims to find out the relationship between gadgets and the effectiveness of learning during the COVID-19 pandemic. It focused onthe readiness of digital infrastructure institutions and the readiness of students in online learning activities during the COVID-19 pandemic. A descriptive qualitative approach was used to describe the roles of gadgets as a learning resource to support effective learning and improve learning outcomes, withliterature review related to the topic. Keywords: Gadgets, Effective, Learning Resources, e-Learning